The Effect of Placement and Workload on Turnover Intention at PT Mega Akbar Superindo - Christiant Eka Wiratama; Sunardi Sembiring Brahmana (DINASTI RESEARCH, 2025)
Every company, in running its business, cannot ignore the importance of managing the human resources it seeks. Issues related to human resources are crucial to a company's operations and its success in achieving its goals, as goals are achieved only when employees perform their jobs well.The purpose of this research is to identify specific factors influencing turnover intention and to find effective solutions to improve employee retention. One approach is to improve appropriate job placement and better workload management. Therefore, this research will investigate The Effect of Placement and Workload on Turnover Intention at PT Mega Akbar Superindo. The research method is quantitative associative, the sampling technique used in this study is non-probability sampling, the data analysis test of this research uses Multiple Linear Regression analysis, Determination Coefficient, Goodness Fit Model Test (F Test), Individual Significance Test (t-Statistic Test). The results of the research show that Job Placement has a positive effect on turnover intention, Workload has a negative effect on turnover intention, Placement and workload have a significant effect on turnover intention. at PT Mega Akbar Superindo.